2004
DOI: 10.1074/jbc.m314274200
|View full text |Cite
|
Sign up to set email alerts
|

A Threshold Mechanism Governing Activation of the Developmental Regulatory Protein σF in Bacillus subtilis

Abstract: The RNA polymerase sigma factor F is a developmental regulatory protein that is activated in a cell-specific manner following the formation of the polar septum during the process of spore formation in the bacterium Bacillus subtilis. Activation of F depends on the membrane-bound phosphatase SpoIIE, which localizes to the septum, and on the formation of the polar septum itself. SpoIIE is responsible for dephosphorylating and thereby activating the phosphoprotein SpoIIAA, which, in turn, triggers the release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 49 publications
(81 reference statements)
4
89
2
Order By: Relevance
“…Consistent with the checkpoint model, a number of studies have found missense mutations in SpoIIE that uncouple asymmetric division from F activation (32,73,111). Indeed, one study tested the in vitro phosphatase activity of the mutant proteins and found that it was similar to that of the wild-type protein (73), further supporting the concept that SpoIIE is subject to a phosphatase-independent regulatory step that couples asymmetric division to F activation.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 61%
See 1 more Smart Citation
“…Consistent with the checkpoint model, a number of studies have found missense mutations in SpoIIE that uncouple asymmetric division from F activation (32,73,111). Indeed, one study tested the in vitro phosphatase activity of the mutant proteins and found that it was similar to that of the wild-type protein (73), further supporting the concept that SpoIIE is subject to a phosphatase-independent regulatory step that couples asymmetric division to F activation.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 61%
“…However, how the cell prevented the dephosphorylated SpoIIAA from activating F in the predivisional cell remained mysterious. A recent study has provided evidence that SpoIIAB, it its ADP-bound state, can serve as a "sink" absorbing SpoIIAA in the cell until a threshold level is reached (32). Precisely why asymmetric division allows the threshold level of dephosphorylated SpoIIAA to be crossed in the prespore is unknown; some speculate that the phosphatase activity of SpoIIE is stimulated by asymmetric division (73), whereas others think that equivalent inheritance of SpoIIE in the two compartments creates a favorable SpoIIE/SpoIIAA-PO 4 ratio in the prespore (32).…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 99%
“…Proteins were separated by SDS-PAGE on 12.5% polyacrylamide gels, electroblotted onto Immobilon-P membranes (Millipore), and blocked in 5% nonfat milk in phosphate-buffered saline (PBS) and 0.5% Tween-20. The blocked membranes were probed with affinity-purified anti-His (1:1000; Santa Cruz Biotechnology), anti-FisB (1:10,000), and anti-s F (15,000) (Carniol et al 2004) diluted into 3% BSA in 13 PBS-0.05% Tween-20. Primary antibodies were detected using horseradish peroxidase-conjugated goat anti-rabbit G (Bio-Rad) and the Western Lightning reagent kit as described by the manufacturer (PerkinElmer).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…T iming of events in many cellular processes, such as cell-cycle control (1-3), cell differentiation (4,5), sporulation (6,7), apoptosis (8,9), development (10,11), temporal order of gene expression (12)(13)(14), and so on, depend on regulatory proteins reaching critical threshold levels. Triggering of these events in single cells is influenced by fluctuations in protein levels that arise naturally due to noise in gene expression (15)(16)(17)(18).…”
mentioning
confidence: 99%